Production Of Liquid Biofuel From Sludge Palm Oil (SPO) Using Heterogeneous Catalytic Pyrolysis - Ali S.H.; Hafriz R.S.R.M.; Shamsuddin A.H.; Salmiaton A. (Tamkang University, 2024)
Sludge palm oil (SPO) is waste generated in the palm oil industry. The discharge of SPO together with palm oil mill effluent has created a major problem due to its difficulty in the treatment process. The feasibility of SPO as a raw material for biofuel production was investigated via catalytic pyrolysis process using heterogeneous Malaysian dolomite catalyst. The effects of operating temperatures and reaction times in the catalytic pyrolysis using Malaysian dolomite catalyst were assessed. The condition for the reaction parameters investigated is as followed: operating temperatures of 350 ?C, 400 ?C, and 450 ?C, reaction times of 30, 45 and 60 minutes, under a constant of 100 ml/min of nitrogen flow rate and 5 wt.% catalyst loading. At a reaction temperature of 350 ?C the SPO conversion was very low even at longer reaction times. The longer reaction times gave higher SPO conversion at an operating temperature of 400 C with the range of conversion between 45.7 to 58.3 wt.%. At temperature 450 ?C the conversion achieved an average of 93.1 1.0 wt.%. Only a slight change at longer times was observed at this temperature. At a temperature of 400 ?C and 45 min of reaction times, the pyro-oil obtained from the process contained the highest hydrocarbon content (83.90 %) and lowest oxygenated compound content (16.10 %), even though the conversion was lower than at 450 ?C. The product selectivity was highest in the diesel range at the reaction temperature of 400 ?C. Thus, with further improvement in catalyst modification together with optimized operating conditions, SPO can be used as a feedstock in the catalytic pyrolysis for producing biofuel in the range carbon number of diesel, gasoline and kerosene. The Author(s).